Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T17:44:29+01:00
A)
x²-(x-2)²=16
x²-(x²-4x+4)=16
x²-x²+4x=16+4
4x=20
x=5

b)
3(x-1)²-3x(x-5)=21
3(x²-2x+1)-3x²+15x=21
3x²-6x+3-3x²+15x=21
9x=21-3
9x=18
x=2

c)
x(x-1)=(x+1)²+2
x²-x=x²+2x+1+2
x²-x-x²-2x=3
-3x=3
x=-1

d)
(x-3)²=(x-1)(x+2)-3
x²-6x+9=x²+2x-x-2-3
x²-6x-x²-x=-5-9
-7x=-14 /*(-1)
7x=14
x=2

e)
(x+1)²-(x-1)(x+1)=6
x²+2x+1-x²+1=6
2x=4
x=2

f)(x-3)²-x²=3
x²-6x+9-x²=3
6x=3-9
6x=-6
x=-1

g)(x-0,2)²=x²-0,44
x²-0,4x+0,04=x²-0,44
x²-0,4x-x²=-0,44-0,04
-0,4x=-0,48 /*(-1)
0,4x=0,48
x=1,2

h)(x+0,1)(x-0,1)=(x-0,1)²
x²-0,01=x²-0,2x+0,01
x²-x²+0,2x=0,01+0,01
0,2x=0,02
x=0,1
2009-12-08T17:46:13+01:00
A)x²-(x-2)²=16
x²-x²-4x+4=16
-4x=16-4
-4x=12/:(-4)
x=-3

b)3(x-1)²-3x(x-5)=21
3(x²-2x+1)-3x²+15x=21
3x²-6x+3-3x²+15x=21
3x²-6x-3x²+15x=21-3
9x=18/:9
x=2

c)x(x-1)=(x+1)²+2
x²-x=x²+2x+1+2
x²-x-x²-2x=2+1
-3x=3/:(-3)
x=-1

d)(x-3)²=(x-1)(x+2)-3
x²-6x+9=x²+2x-x-2-3
x²-6x-x²-2x+x=-2-3-9
-7x=-14/(-7)
x=2

e)(x+1)²-(x-1)(x+1)=6
x²+2x+1-x²-1=6
x²+2x-x²=6-1+1
2x=6/2
x=3

f)(x-3)²-x²=3
x²-6x+9-x²=3
-6x=3-9
-6x=-6/(-6)
x=1

g)(x-0,2)²=x²-0,44
x²-0,4x+0,04=x²-0,44
x²-0,4x-x²=-0,44-0,04
-0,4x=-0,48/(-0,4)
x=1,2

h)(x+0,1)(x-0,1)=(x-0,1)²
x²-0,01=x²-0,2x+0,01
x²-x²+0,2x=0,01+0,01
0,2x=0,02/0,2
x=0,1


2009-12-08T17:46:34+01:00
A)x² - (x-2)² = 16
x² - (x² - 4x + 4) = 16
x² - x² + 4x - 4 = 16
4x = 16+4
4x = 20 |:4
x = 5

b)3(x-1)²-3x(x-5)=21
3(x² - 2x +1²) - 3x² + 15x = 21
3x² - 6x + 3 - 3x² + 15x = 21
-6x + 15x = 21 -3
9x = 18 |:9
x = 2

c)x(x-1)=(x+1)²+2
x² - x = x² + 2x + 1² + 2
x² - x - x² - 2x = 1 + 2
-x = 3 |*(-1)
x = -3

d)(x-3)²=(x-1)(x+2)-3
x² - 2*3x + 3² = x² +2x -x - 2 - 3
x² - 6x + 9 = x² + 2x - x - 5
x² - x² - 6x -2x + x = - 5 - 9
-7x = -14 |:(-7)
x = 2

e)(x+1)²-(x-1)(x+1)=6
x² + 2*1*x + 1² - x² - 1² = 6
x² + 2x + 1 - x² - 1 = 6
2x = 6 - 1 + 1
2x = 6 |:2
x = 3

f)(x-3)²-x²=3
x² - 2*3*x + 3² - x² = 3
x² - 6x + 9 - x² = 3
-6x = 3 - 9
-6x = -6 |:(-6)
x = 1

g)(x-0,2)²=x²-0,44
x² - 2*0,2*x + 0,2² = x² - 0,44
x² - 0,4x + 0,04 = x² - 0,44
x² - x² - 0,4x = -0,44 - 0,04
-0,4x = -0,48 |:(-0,4)
x = 1,2

h)(x+0,1)(x-0,1)=(x-0,1)²
x²-0,01=x²-0,2x+0,01
x²-x²+0,2x=0,01+0,01
0,2x = 0,02 |:0,2
x = 0,1